Klasifikasi Kepuasan Pelanggan Terhadap Platform E-Commerce dengan Metode K–Nearest Neighbor (K-NN) - Halim, Tio Novian; Martin, Ryan; Hutasoit, Rista Kesia Br; Aisyah, Siti (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
This study aims to determine customer satisfaction, towards e-commerce platforms. E-commerce is a platform that can make various types of payments and purchases online from a smartphone. This research is a quantitative approach using survey techniques, namely by distributing questionnaires. The data used uses primary data in the form of a questionnaire obtained through google form. Sampling using Convenience Sampling technique so that a research sample of 1001 respondents was obtained. Data processing in this study using the K-Nearest Neighbor (K-NN) method, the results showed that customer satisfaction had a significant effect on e-commerce both partially. based on training and data processing calculations of the K-NN model, the two best e-commerce were obtained according to the respondents' assessment, namely Shopee and TokoPedia, with a percentage of Shopee 82.98% of 779 total respondents and TokoPedia 80.30% of 133 total respondents.